Racial disparity in excess mortality in Brazil during COVID-19 times. (17th June 2021) - Marinho, Maria Fatima; Torrens, Ana; Teixeira, Renato; Brant, Luisa Campos Caldeira; Malta, Deborah Carvalho; Nascimento, Bruno Ramos; Ribeiro, Antonio Luiz Pinho; Delaney, Richard; de Paula, Pedro do Carmo Baumgratz; Setel, Philip; Sampaio, Jhames Matos; Nogales-Vasconcelos, Ana Maria
Abstract: We evaluated the impact of the COVID-19 pandemic on excess mortality by race/skin colour in Brazil, between epidemiological weeks 12 and 50 of 2020. We compared the 2020 point estimate and the expected point estimate applying 2019 mortality rates to the 2020 population. There was an excess of 187 002 deaths (+20.2%) compared to the expected. Excess mortality was 26.3% (23.3–29.3%) among blacks/browns compared to 15.1% (14.1–16.1%) among whites (58.9% of excess among black/browns). Age-standardized rates increased from 377 to 419/100 000 among blacks/browns compared to 328 to 398/100 000 in whites, resulting in 9% relative risk. Excess mortality in Brazil depicts a considerable gap, with increased mortality in all age groups in the black/brown population.